2019
DOI: 10.1111/jvp.12819
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, tissue residues, and ex vivo pharmacodynamics of tylosin against Mycoplasma anatis in ducks

Abstract: The pharmacokinetics of tylosin were investigated in 3 groups of ducks (n = 6). They received a single dose of tylosin (50 mg/kg) by intravenous (IV), intramuscular (IM), and oral administrations, respectively. Plasma samples were collected at various time points to 24 hr post‐administration to evaluate tylosin concentration over time. Additionally, tylosin residues in tissues and its withdrawal time were assessed using 30 ducks which received tylosin orally (50 mg/kg) once daily for 5 consecutive days. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
4
5
0
Order By: Relevance
“…After IM injection at 10 mg/kg, TT reached a C max of 10.76 µg/mL at 0.25 h (T max ), after being rapidly absorbed into the serum. Although the information about pharmacokinetics of TT after IM injection in other fish may not be applicable to this study, the rapid rate of absorption was similar to the values reported (T max within 1 h) in ducks, cattle, buffaloes, and sheep [ 14 , 17 , 32 ]. The dose-normalized exposure (AUC) in olive flounder (123.55 µg/mL*h at 10 mg/kg) was 32-fold greater than the one found in the previous study (duck) that used intramuscular administration of the TT (19.14 µg/mL*h after 50 mg/kg) [ 14 ], which prolonged the duration of action as evidenced by the large exposure (AUC).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…After IM injection at 10 mg/kg, TT reached a C max of 10.76 µg/mL at 0.25 h (T max ), after being rapidly absorbed into the serum. Although the information about pharmacokinetics of TT after IM injection in other fish may not be applicable to this study, the rapid rate of absorption was similar to the values reported (T max within 1 h) in ducks, cattle, buffaloes, and sheep [ 14 , 17 , 32 ]. The dose-normalized exposure (AUC) in olive flounder (123.55 µg/mL*h at 10 mg/kg) was 32-fold greater than the one found in the previous study (duck) that used intramuscular administration of the TT (19.14 µg/mL*h after 50 mg/kg) [ 14 ], which prolonged the duration of action as evidenced by the large exposure (AUC).…”
Section: Discussionsupporting
confidence: 76%
“…Although the information about pharmacokinetics of TT after IM injection in other fish may not be applicable to this study, the rapid rate of absorption was similar to the values reported (T max within 1 h) in ducks, cattle, buffaloes, and sheep [ 14 , 17 , 32 ]. The dose-normalized exposure (AUC) in olive flounder (123.55 µg/mL*h at 10 mg/kg) was 32-fold greater than the one found in the previous study (duck) that used intramuscular administration of the TT (19.14 µg/mL*h after 50 mg/kg) [ 14 ], which prolonged the duration of action as evidenced by the large exposure (AUC). The F of TT was calculated to be 87.35% in P. olivaceus after IM injection at 10 mg/kg, supporting the rapid and nearly complete absorption following IM administration.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations